2013
DOI: 10.1080/10503307.2013.829253
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal differentiation within depression diagnosis: Relating interpersonal subgroups to symptom load and the quality of the early therapeutic alliance

Abstract: We examined interpersonal problems in psychotherapy outpatients with a principal diagnosis of a depressive disorder in routine care (n=361). These patients were compared to a normative non-clinical sample and to outpatients with other principal diagnoses (n=959). Furthermore, these patients were statistically assigned to interpersonally defined subgroups that were compared regarding symptoms and the quality of the early alliance. The sample of depressive patients reported higher levels of interpersonal problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 54 publications
6
44
0
Order By: Relevance
“…Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011;Salzer et al, 2011Salzer et al, , 2008; our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006).…”
Section: Psychopathology and Interpersonal Problemssupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011;Salzer et al, 2011Salzer et al, , 2008; our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006).…”
Section: Psychopathology and Interpersonal Problemssupporting
confidence: 82%
“…Due to methodological and reporting limitations of many of these studies, conclusions regarding profile descriptors are difficult to draw. In general, these studies suggest that major depressive disorder has a nonassertive and socially avoidant style (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006), social phobia has a nonassertive style (Cain et al, 2010;Kachin et al, 2001;Stangier et al, 2006), and generalized anxiety disorder has an exploitable style (Przeworski et al, 2011;Salzer et al, 2008Salzer et al, , 2011. These disorders also seem to have marked elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on posttraumatic stress disorder (PTSD; Thomas et al, 2014) and GAD (Przeworski et al, 2011) identified four empirically derived interpersonal clusters arrayed around the quadrants of the circumplex (warm-dominant, warm-submissive, cold-submissive, and cold-dominant). Studies focusing on depression identified six (Cain et al, 2012) and eight (Grosse Holtforth et al, 2014) clusters. Despite differences between the two or more interpersonal clusters solutions, the overall message is that interpersonal heterogeneity appears to exist within specific disorders.…”
mentioning
confidence: 99%
“…Furthermore, Couto, Vandenberghe, Tavares, and Silva (2012) found relationships between interpersonal traits and social skills, while Cain et al (2012) showed that these traits can influence the course of depression and delay its remission. Grosse Holtforth et al (2014) found an association between interpersonal problems, depressive symptoms and the quality of the therapeutic alliance in psychotherapy. Interpersonal traits also predict the effect of treatment in patients with obesity problems (Lo Coco, Gullo, Scrima, & Bruno, 2012).…”
mentioning
confidence: 99%